Dover Micro Open Street Events: Evaluation Results and Implications for Community-Based Physical Activity Programming - Suminski, Richard R.; Jackson-Short, Chanda; Duckworth, Noel; Plautz, Eric; Speakman, Karen; Landgraf, Rita; Patterson, Freda (Frontiers in Public Health, 2019)
Background: Open Streets events provide opportunities for residents to be active. Methods: The current program developed and implemented five smaller scale, Micro Open Streets Events (MOSE) in Dover, DE that provided a range of opportunities for physical activity over a <0.5 miles stretch of closed road. Our objective was to evaluate the capacity of this approach to reach residents and improve knowledge and intention to engage in physical activity once the event was over. We used individual surveys, observational, and neighborhood audit factors to assess MOSE participation and conduciveness to physical activity. Results: Our results showed that MOSE attendance ranged from 40-500 adults from a high-risk demographic (i.e., non-Caucasian, middle-age, overweight), who demonstrated a strong liking of the MOSE and increased knowledge of, and intention to engage in physical activity following the event. Conclusions: Our data suggest that where a full-scale Open Streets event is not feasible, a MOSE may be a viable alternative.